Observer-based temperature control of an LED heated silicon wafer. (October 2018) - Kleindienst, Martin; Reichhartinger, Markus; Horn, Martin; Staudegger, Felix
Highlights: A novel model-based rapid thermal processing (RTP) approach is proposed. A detailed mathematical model of the heat-up process is presented. An observer is designed to estimate the wafer's temperature profile. A systematic procedure allows to avoid the effect of controller windup. Abstract: The key issue in semiconductor rapid thermal processing (RTP), where silicon wafers are heated to desired temperatures, is to ensure uniform wafer temperature profiles. This in turn guarantees that the manufactured integrated circuits (IC), which are spread over the entire wafer, can be processed in an equal measure. In this study, a mathematical model capturing the physical behavior of the heating-up process is presented. It relies mainly on the well-known partial differential heat equation, governing the temperature distribution in a given region of a given material. Based on this, an observer as also a control law is proposed, which in combination turned out to be superior to conventional RTP strategies. The approach is validated in practice at a real world heating system with different wafer types.